Knowledge, Perceptions, and Behaviors Related to Salt Use Among Philadelphia Chinese Take-Out Restaurant Owners and Chefs. Issue 5 (September 2014) - Ma, Grace X.; Shive, Steve; Zhang, Yolanda; Aquilante, Jennifer; Tan, Yin; Zhao, Mei; Solomon, Sara; Zhu, Steven; Toubbeh, Jamil; Colby, Lisa; Mallya, Giridhar; Zeng, Qiaoling
Most of the sodium Americans consume comes from processed and restaurant foods. An upstream global strategy to promote health is to work with local restaurants to reduce sodium content in their food offerings, while accounting for food taste and economic considerations. In urban communities, Chinese take-out restaurants serve meals with large amounts of sodium and are clustered in low-income, racial/ethnic minority communities with a high prevalence of hypertension. The objective of this study is to assess baseline knowledge, attitudes, and behaviors related to sodium use/consumption among Chinese take-out owners and chefs recruited to participate in the Philadelphia Healthy Chinese Take-Out Initiative. A cross-sectional study of 221 Chinese take-out restaurants was conducted from August 2012 to February 2013. Items measured knowledge, attitudes, and behaviors related to salt use, salt consumption, and health. Most owners/chefs knew that excess sodium consumption contributes to high blood pressure but were less aware of other health effects and of major sources of sodium in the U.S. diet. The majority were willing and able to reduce sodium content in meals if customer demand could be maintained, and they desired training in food preparation, procurement, and marketing. Findings show a need to provide education, strategies, and support to Chinese take-out owners/chefs in preparing low-salt dishes. The results of this and future studies to reduce sodium content in meals by working with restaurant owners and chefs have global health promotion implications.